Faktor Risiko Diabetes Mellitus pada Remaja SMA Lab Salatiga dan SMK Kristen BM Salatiga dengan Obesitas dan Nonobesitas di Kota Salatiga - Ngana, Anggu Rambu Dawi; Agustina, Venti; Messakh, Sanfia Tesabela (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Diabetes Mellitus (DM) is a degenerative disease triggered by unhealthy lifestyles such as obesity. Obesity is a condition of someone who has a body weight above normal or more than the Body Mass Index (BMI) value of 27 kg/m2. Obesity is prone to occur in adolescence. The purpose of this study was to identify risk factors for diabetes mellitus (DM) in obese adolescents.Methods: The method used was descriptive quantitative with a cross sectional approach conducted in October-December 2020 on adolescents at SMA Lab Salatiga and SMK Kristen BM Salatiga. The samples in this study were adolescents with obesity at SMA Lab Salatiga and SMK Kristen BM Salatiga. The data collection technique in this study used google form. The research data were processed using SPSS (Univariate and Chi Square Test).Results: From the results of the study, several factors of DM were found, including age, gender, family history of Diabetes Mellitus. There were 50.8% of respondents who had normal blood pressure and most of the blood sugar levels were normal (57.1%). In this study, diet and physical activity had no relationship with obesity. The results of the analysis using chi square obtained a p-value (p>0,05).Conclusion: Factors of diabetes mellitus (DM) include age, gender and family history of diabetes mellitus while blood pressure, obesity diet, physical activity do not jeopardize the occurrence of diabetes mellitus and diet.